A study to find the correlation between mucocutaneous manifestations and CD4 counts among the newly diagnosed HIV individuals. - Subhodha Kumar Patjoshi; T Jaya Chandra (International Journal of Medical Research and Review, 2020)
Introduction: Skin disorders are common manifestations of HIV disease. A study was conducted to find the correlation between the degree of immunosuppression and the incidence of specific skin disorders in patients with HIV infection.Materials and methods: Study was conducted in the department of dermatology, SCB Medical College and Hospital, Cuttack from October 2010 to September 2012. Random sampling was considered in this study. Referred patients, after pretest counseling at ICTC Centre, were included and individuals who are on antiretroviral treatment were excluded. Relevant diagnostic tests were performed like scraping and KOH examination for the diagnosis of dermatophytoses and candidiasis, Tzanck smear for herpes infection, Darkfield microscopy for diagnosis of a syphilitic ulcer, Biopsy is done wherever required. CD4 count was done as per the guidelines.Results: A total of 150 (100%) participants were included, the male-female ratio was 1.8. Age-wise, 57% (85) were included in 31–45 group and 15% were unmarried. Fungal infections constitute 17.9% of total mucocutaneous disorders followed by bacterial infections (10.5%), viral (8.09%) and parasitic (6.7%) infestations.Conclusion: Age group, 31–45 years is the commonest for HIV infection. Fungal infections (dermatoses) of the skin were most common followed by bacterial folliculitis, herpes zoster, and scabies. Except for viral infections, the mean CD4 counts were <200cells/cu mm.